UOT OF DENTISTS-ORTHOPEADISTS WORK OVER IMPLANTOLOGIC RECEPTION. REMOVABLE AND CONDITIONALLY REMOVABLE CONSTRUCTIONS - E.V. Diiev; T. V. Diieva; V. V Lepsky; V. V. Lepsky; V. A. Labunets (Ukrainian Medical Stomatological Academy, 2017)
Complete removable and conditionally removable dentures with implant fixation have a wide variety of application within the public health in our country. However, unlike traditional methods of patients' prosthesis with complete edentia, methods of dental implantation in Ukraine do not have full legal status because of the lack of clinical technological protocols and complete lack of departmental time standards for doctors- orthopedists on their production. The research aim To establish the value of UOT orthopedic doctors work in the manufacture of removable and conditionally removable dentures locked on implants. Materials and methods The object of study is the clinical processes of manufacturing removable and conditionally removable dentures locked on implants; Methods To determine the nature and structure of the cost of the dentist-orthopedist labor in manufacturing of removable and conditionally removable constructions locked on implants; to determine the total length of relevant clinical stages of the removable and conditionally removable constructions locked on implants production; for the determination of UOT of the dentists-orthopedists in manufacturing these types of dentures; to handle the study. To determine UOT of doctors-orthopedists in manufacturing removable and conditionally removable dentures locked on implants the officially approved by the Ministry of Health of Ukraine methods of installation labor costs in prosthetic dentistry in Labunets V.A. (1999) [15] modification was used. The transfer of received standard of time (ST) in UOT held by the formula: UOT = Tst ÷ T1uot The value of T1uot was chosen on probation and is equal to the objective length of time duration for the production of the conditional construction. In this case, it takes 60 minutes - the time to manufacture one conventionally pressed crown. The chronometry results of measuring of the processes of clinical manufacturing by 6 dentists- orthopedists 10 complete removable dentures with fixation on spherical abutment, 5 dentists-orthopedists 7 full dentures with radar-abutment fixation, 9 doctors who conducted the prosthesis with 13 complete dentures with beam fixation, 4 orthopedists who produced 8 complete removable dentures on telescopes and 10 dentists with 15 conditionally removable dentures, gave the possibility to calculate the average and actual time standards for dentists-orthopedists to manufacture these types of dentures, which revealed that the average norms of time do not match to the actual amount of time, thus in manufacturing of the dentures that are made on 2-3 implant supports they are lower than factual, and comparatively to prostheses made on 4-6 points of fixation on implants, it exceeds. The standard time for the dentists to manufacture complete removable dentures with fixation on implants are set basing on the average time standards, which do not match the standards of the time that are established on the basis of the actual performance of the production of these types of dentures. In the manufacturing of complete removable reinforced dentures with fixation on one-stage implants with spherical abutments or conditionally removable dentures, average and actual value of standard of time exceeds only partially.